Business development for Bakpia SMEs using digital marketing in Kojor Hamlet, Bojong Village - R. Arri Widyanto; Rohmat Sigit Ribowo; Naufal Gufron; Ade Adams; Puji Agustina; Dwi Setya Rini (Community Empowerment, 2022)
A home industry in the form of bakpia, cukil bread, rengginang, chiffon cake, and celery sticks exists in Kojor Hamlet, Bojong Village, Mungkid District, Magelang Regency. During the pandemic, many MSMEs experienced a loss in profits or had to close their doors. One of them is Mbak Pur's Bakpia MSME, which has seen a 66 percent decrease in turnover. The addition of a new product in the form of chiffon cake is one of the efforts to fight the drop in turnover. However, because it has not been properly packaged and does not have an SPP-IRT permit, this new product is not widely known by the general public. This program employs a participatory community empowerment model, also known as Participatory Rural Appraisal (PRA), which necessitates active participation from partners. Partners play an active role by providing space, consumables, and equipment. Alternative marketing models, such as digital marketing using social media, new product packaging, and NIB and SPP-IRT licensing, were achieved as a result of the program.